Neo-corporatism and political parties - Becker, Joachim (Teorija in praksa, 2025)
The article analyses the rise, erosion and contestation of neo-corporatism in Austria and Slovenia from a régulationist perspective to highlight the role of political parties. The various relationships between key organisations of capital and labour on one hand and political parties on the other are shown to play a key role in understanding the different dynamics of the contesting of neo-corporatism in the two countries. While organisations of capital and labour have strong links with political parties in Austria, this is not the case in Slovenia. These distinctions have led to a crucial difference in the phase of declining neo-corporatism. The links between organisations of capital and labour with major political parties have contributed to the (precarious) institutional stabilisation of neo-corporatist arrangements in Austria, whereas in Slovenia the key right-wing party managed to destabilise a vital pillar of neo-corporatism.
Keywords: Austria; Avstrija; Ekonomska politika; neo-corporatism; neokorporativizem; political parties; politične stranke; Politični sistemi; Slovenia; Slovenija